COMPOSTO A BASE DE ESTERCO BOVINO E FIBRA DE COCO COMO SUBSTRATOS SUSTENTÁVEIS NA PRODUÇÃO DE MUDAS DE CORDIA GLABRATA(MART). - VIEIRA, Jéssica Dionizio; ESPINDOLA, Gabriella Almeida dos Santos; RODRIGUES, Pedro Henrique Dias; NUNES, Igor Barros; REGO, Norton Hayd (ANAIS DO ENIC, 2025)
-